An interactive surgical simulation tool to assess the consequences of a partial glossectomy on a biomechanical model of the tongue. Issue 8 (11th June 2019) - Kappert, K.D.R.; van Alphen, M.J.A.; van Dijk, S.; Smeele, L.E.; Balm, A.J.M.; van der Heijden, F.
Abstract: Oral cancer surgery has a negative influence on the quality of life (QOL). As a result of the complex physiology involved in oral functions, estimation of surgical effects on functionality remains difficult. We present a user-friendly biomechanical simulation of tongue surgery, including closure with suturing and scar formation, followed by an automated adaptation of a finite element (FE) model to the shape of the tongue. Different configurations of our FE model were evaluated and compared to a well-established FE model. We showed that the post-operative impairment as predicted by our model was qualitatively comparable to a patient case for five different tongue maneuvers.